Assessing residential land cover dynamics in Medan Deli Sub-district, Medan City from 2014 to 2024 using GIS technology - Syahru Ramadhan; Rahmawaty; Abdul Rauf; Siti Aekbal Salleh; Mohd Hasmadi Ismail; Agus Purwoko; Razali; Suranto (Talenta Publisher, 2026)
Urban growth in Medan Deli Sub-district has intensified demand for settlement land and increased pressure on remaining non-built-up land. This study quantified settlement land cover dynamics in 2014, 2019, and 2024 using Landsat 8 Collection 2 surface reflectance imagery processed in Google Earth Engine and GIS-based post-classification comparison. Seven land cover classes were interpreted: water body, mixed garden, open land, mangrove, settlement, shrubs, and pond. The settlement class remained dominant in all observation years and increased from 1,443.67 ha (74.27%) in 2014 to 1,446.04 ha (74.39%) in 2019 and 1,505.77 ha (77.46%) in 2024. The net settlement expansion during 2014-2024 was 62.10 ha, with the largest gross conversions to settlement originating from open land (114.43 ha), mixed garden (46.65 ha), shrubs (16.96 ha), mangrove (4.29 ha), pond (1.52 ha), and water body (1.17 ha). The change matrix also shows that 122.93 ha of land classified as settlement in 2014 shifted to other classes by 2024, indicating heterogeneous urban land-cover dynamics rather than one-directional expansion alone. These results highlight the need to limit settlement growth, protect green and water-sensitive areas, and incorporate remote-sensing-based monitoring into urban spatial planning in coastal Medan